An effective method to extract and purify radiolaria from tropical marine sediments - Zhang, Qiang; Swann, George E. A. (Frontiers in Marine Science, 2023)
Radiolaria are the primary contributors to biogenic opal in the tropical ocean, and their isotope compositions are potentially useful tool for reconstructing the silicon cycle in mid-depth waters. To date little attention has been paid to their isotopic study, partly because of the difficulties in purifying radiolarian tests from marine sediments. In this study twelve surface sediment samples from the South China Sea and the western Indian Ocean were used in a density separation experiment, with the aim of enabling better separation of radiolarian tests from detrital grains and other siliceous organisms. The results show that sponge spicules, radiolarian tests and diatom frustules from tropical ocean sediments preferentially settle in heavy liquid solutions with different specific gravities, and are constrained to range in the densities from 1.95 to 2.1 g/cm3, 1.85 to 2.0 g/cm3 and 1.7 to 1.95 g/cm3, respectively. These density ranges for radiolarians and diatom frustules in the low-latitude ocean are much lower than that of amorphous silica, probably resulting from the decreased silicification of radiolarians and diatoms due to the limited silica availability in the highly-stratified tropical ocean. According to the components and density ranges of siliceous microfossils observed in this study, an optimized method with detailed procedures is proposed to extract and purify radiolarians from late Quaternary sediments in the tropical ocean that have not undergone substantial dissolution and diagenetic change. Using a combination of wet-chemical treatment, wet sieving, differential settling, and density separations, this method can yield clean radiolarian test in sufficient quantities from tropical ocean sediments for isotope/geochemical analysis.